2017
DOI: 10.1038/s41598-017-09797-8
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir protects Zika virus-infected mice from mortality, preventing short- and long-term sequelae

Abstract: Zika virus (ZIKV) causes significant public health concerns because of its association with congenital malformations, neurological disorders in adults, and, more recently, death. Considering the necessity to mitigate ZIKV-associated diseases, antiviral interventions are an urgent necessity. Sofosbuvir, a drug in clinical use against hepatitis C virus (HCV), is among the FDA-approved substances endowed with anti-ZIKV activity. In this work, we further investigated the in vivo activity of sofosbuvir against ZIKV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 33 publications
(49 reference statements)
7
63
1
Order By: Relevance
“…http://dx.doi.org/10.1101/195172 doi: bioRxiv preprint first posted online Sep. 28, 2017; Previous studies have detected ZIKV in the brains of neonatal mice shortly (5-10 dpi) after systemic inoculation (22,54). In agreement, we found that ZIKV subcutaneously inoculated successfully reaches and replicates in the mouse brain, with a replication peak between 6 and 12 dpi.…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is supporting
confidence: 79%
See 1 more Smart Citation
“…http://dx.doi.org/10.1101/195172 doi: bioRxiv preprint first posted online Sep. 28, 2017; Previous studies have detected ZIKV in the brains of neonatal mice shortly (5-10 dpi) after systemic inoculation (22,54). In agreement, we found that ZIKV subcutaneously inoculated successfully reaches and replicates in the mouse brain, with a replication peak between 6 and 12 dpi.…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is supporting
confidence: 79%
“…Here, we report that male and female adult mice infected with ZIKV at post-natal day 3 show impaired performance in the novel object recognition (NOR) task (~90 dpi), a non-rewarded, ethologically relevant paradigm widely used to assess declarative memory in rodents (71). Similar results have recently been reported using two different tasks to evaluate spatial and aversive memories (54). These results strongly suggest that ZIKV-exposed infants might develop learning problems, which can seriously compromise patient's life quality.…”
Section: Cc-by-nc-ndsupporting
confidence: 67%
“…Zika virus treatment and prevention strategies are currently under intense investigation. Antivirals used for treatment of hepatitis C virus such as sofosbuvir and broad‐spectrum antiviral agents such as favipiravir were explored in in vitro and animal models for potential use as treatment of ZIKV infection. Sofosbuvir increased survival and reduced neurological impairment in ZIKV‐infected mice, but studies in humans are still unavailable.…”
Section: Future Prospects and Final Remarksmentioning
confidence: 99%
“…Antivirals used for treatment of hepatitis C virus such as sofosbuvir and broad‐spectrum antiviral agents such as favipiravir were explored in in vitro and animal models for potential use as treatment of ZIKV infection. Sofosbuvir increased survival and reduced neurological impairment in ZIKV‐infected mice, but studies in humans are still unavailable. The antimalarial drug cloroquine inhibits ZIKV infection in vitro and attenuates ZIKV‐associated morbidity, mortality, and fetal microcephaly in mice .…”
Section: Future Prospects and Final Remarksmentioning
confidence: 99%
“…Nevertheless, the in vivo potency of rilpivirine seems better than sofosbuvir, a hepatitis C virus (HCV) nucleoside drug that was reported with anti-ZIKV activity. 9 Specifically, rilpivirine completely protected ZIKV-infected mice from death, whereas sofosbuvir and other nucleoside inhibitors only conferred partial protection. 10 The study by Sariyer et al 2 has provided a good example of repurposing clinical drugs for potential treatment of ZIKV infection.…”
mentioning
confidence: 96%